STRATEGI KAMPANYE PARTAI POLITIK DALAM USAHA PEMULIHAN KEPERCAYAAN MASYARAKAT PADA PEMILU LEGISLATIF 2014 - Ignatius Adiwidjaja; Nanang Bagus Sriharjono (REFORMASI, 2014)
Elections are a means to make the transfer of power and the power of competition. As a democratic mechanism to make the turn leaders, representatives of the people who will sit in the Legislature and the Executive shall be carried out in direct, general, free, and confidential, and based on the spirit of honest and fair. The low public confidence in the political parties are a threat to the successful implementation of the party elections and political parties should find a solution to fix it. Researchers carried out by the Institute of the Centre for Strategic and International Studies (CSIS), the result is: Trust the people against political parties is currently very low. Only 22.4 percent of respondents believed that political parties have a good performance. The number of respondents reached 2,290 people with an estimated margin of error of about 2.1 percent and the 95 percent confidence level. So thus, the political trust of citizens in the Parliament, political parties, and the government is deficit.